Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

Conserved and Unique Protein Expression Patterns Across Reproductive Stage Transitions in Social Hymenopteran Queens - Alison McAfee; Baptiste Martinet; Kimberly Przybyla; Félicien Degueldre; Shelley E. Hoover; Serge Aron; Leonard J. Foster (Molecular Ecology, 2024)
Hymenopteran queens are collectively highly fecund, often long‐lived individuals that undergo dramatic physiological changes after they mate and establish a nest. However, the degree to which these changes are conserved among species with different life histories is not well‐defined. We conducted a comparative proteomic study investigating differences between reproductive stages (virgin, mated and established queens) of Apis mellifera , Bombus impatiens , B. terrestris and Lasius niger . We analysed haemolymph for all species except L. niger , for which a whole‐body analysis was performed due to the small size of these queens. We identified conserved upregulation of proteins involved in anatomical and system development as queens transition to establishing a nest in all species except B. terrestris . We also identified conserved patterns of vitellogenin, vitellogenin receptor and immune‐responsive protein (IRP)30, all of which are proteins typically associated with oviposition. However, expression patterns of other immune proteins, heat‐shock proteins (HSPs), detoxification enzymes and antioxidant enzymes were more dissimilar, with some species exhibiting similar trends and co‐occurrence through reproductive stages, while others exhibited variable or opposite patterns. These conserved and unique profiles likely in part reflect similarities and differences in selective pressure on reproductive stages of each species and may indicate differing abilities to respond to emergent pathogens or environmental change.

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Integrated in vitro models for hepatic safety and metabolism: evaluation of a human Liver-Chip and liver spheroid - Alison J. Foster; Bhavik Chouhan; Sophie L. Regan; Helen Rollison; Sara Amberntsson; Linda C. Andersson; Abhishek Srivastava; Malin Darnell; Jonathan Cairns; Stanley E. Lazic; Kyung-Jin Jang; Debora B. Petropolis; et al. (Archives of Toxicology, 2019)

Utility of spherical human liver microtissues for prediction of clinical drug-induced liver injury - William R. Proctor; Alison J. Foster; Jennifer Vogt; Claire Summers; Brian Middleton; Mark A. Pilling; Daniel Shienson; Monika Kijanska; Simon Ströbel; Jens M. Kelm; Paul Morgan; Simon Messner; et al. (Archives of Toxicology, 2017)

Genomics, transcriptomics and proteomics: enabling insights into social evolution and disease challenges for managed and wild bees - Judith Trapp; Alison McAfee; Leonard J. Foster (Molecular Ecology, 2017)
Globally, there are over 20 000 bee species ( Hymenoptera: Apoidea: Anthophila ) with a host of biologically fascinating characteristics. Although they have long been studied as models for social evolution, recent challenges to bee health (mainly diseases and pesticides) have gathered the attention of both public and research communities. Genome sequences of twelve bee species are now complete or under progress, facilitating the application of additional ‘omic technologies. Here, we review recent developments in honey bee and native bee research in the genomic era. We discuss the progress in genome sequencing and functional annotation, followed by the enabled comparative genomics, proteomics and transcriptomics applications regarding social evolution and health. Finally, we end with comments on future challenges in the postgenomic era.

Hepatic effects of repeated oral administration of diclofenac to hepatic cytochrome P450 reductase null (HRN™) and wild-type mice - James A. Akingbasote; Alison J. Foster; Ian Wilson; Sunil Sarda; Huw B. Jones; J. Gerry Kenna (Archives of Toxicology, 2016)

Survivors, not invaders, control forest development following simulated hurricane - Audrey Barker Plotkin; David Foster; Joel Carlson; Alison Magill (Ecology, 2013)
Wind disturbance profoundly shapes temperate forests but few studies have evaluated patterns and mechanisms of long‐term forest dynamics following major windthrows. In 1990, we initiated a large hurricane simulation experiment in a 0.8‐ha manipulation (pulldown) and 0.6‐ha control area of a maturing Quercus rubra – Acer rubrum forest in New England. We toppled 276 trees in the pulldown, using a winch and cable, in the northwesterly direction of natural treefall from major hurricanes. Eighty percent of canopy trees and two‐thirds of all trees ≥5 cm dbh (diameter at breast height) suffered direct and indirect damage. We used 20 years of measurements to evaluate the trajectory and mechanisms of forest response after intense disturbance. Based on the patch size and disturbance magnitude, we expected pioneer tree and understory species to drive succession. The first decade of analyses emphasized tree seedling establishment and sprouting by damaged trees as the dominant mechanisms of forest recovery in this extensive damaged area. However, despite 80% canopy damage and 8000‐m 2 patch size, surviving overstory and advance regeneration controlled longer‐term forest development. Residual oaks make up 42% of stand basal area after 20 years. The new cohort of trees, dominated by black birch advance regeneration, contributes 30% of stand basal area. There were shifts in understory vegetation composition and cover, but few species were gained or lost after 20 years. Stand productivity rebounded quickly (litterfall recovered to pre‐disturbance levels in six years), but we predict that basal area in the pulldown will lag behind the control (which gained 6 m 2 /ha over 20 years) for decades to come. This controlled experiment showed that although the scale and intensity of damage were great, abundant advance regeneration, understory vegetation, and damaged trees remained, allowing the forest to resist changes in ecosystem processes and invasion by new species.

Improved PCR-based Assays for Pre-symptomatic Diagnosis of Light Leaf Spot and Determination of Mating Type of Pyrenopeziza Brassicae on Winter Oilseed Rape - Simon J. Foster; Alison M. Ashby; Bruce D.L. Fitt (European Journal of Plant Pathology, 2002)

The discriminative stimulus properties of self-administered ethanol are mediated by GABA A and NMDA receptors in rats - Clyde W. Hodge; Amy A. Cox; Alison M. Bratt; Rosana Camarini; Kimberly Iller; Stephen P. Kelley; Kristin K. Mehmert; Michelle A. Nannini; M. Foster Olive (Psychopharmacology, 2001)